Prompt engineering for everybody with ChatGPT and GPT4. (Packt Publishing, 2023)
Prompt engineering is strategically designing and modifying prompts used in ChatGPT to achieve desired outputs and crafting prompts that provide clear instructions, relevant context, or specific constraints to guide the generation process. The course begins with an introduction to prompt engineering and then briefly covers the course overview and objectives and any additional resources available in the course. We then move over to the basics of prompt engineering in further detail, including inputs, outputs, parameters, and learning to craft simple prompts. We will then evaluate the prompts and the best practices and tricks in prompts engineering techniques, Chain-of-Thought prompting, multilingual and multimodal prompts, and the non-deterministic nature of AI and human-AI collaboration. We will automate emails and social media posts and generate content in blogs, articles, and reports. We will indulge in creative writing and brainstorming to generate ideas and drafts, efficient research and information curation, task management, and decision-making. We will explore fairness and reducing bias, privacy, and data security. Upon completing the course, we will look at real-life scenarios and use cases for AI, learn to use prompt engineering, and practice newly learned techniques to leverage the power of prompts in ChatGPT. What You Will Learn Understand the basics and how to create prompts as a skill Discover role and nested prompting and advanced prompt engineering Learn about multilingual and multimodal AI systems Automate emails, social media posts, and write blogs and reports Learn creative writing, brainstorming, manage tasks/decision-making Learn about the responsible use of AI and ethical considerations Audience This course is designed to cater to technical and nontechnical individuals looking to join the AI revolution soon. Avid learners that want to stay ahead of the curve and enhance their skills to achieve their maximum potential using AI tools, trainers and educators, managers, researchers, data analysts, creative writers, bloggers, social media managers, human resource officers, auditors, sales representatives, marketing specialists, copywriters, and project managers can benefit from this course. This course does not have any specific prerequisites other than basic computer knowledge. About The Author Andrei Gheorghiu: Andrei Gheorghiu is an experienced trainer, passionate about helping learners achieve their maximum potential. With a background in IT audit, information security, and IT service management, he has delivered training to over 10,000 students across different industries and countries. He brings expertise and empathy to his teaching as a trainer and quality reviewer of accredited ITIL training courses. He is also a Certified Information Systems Security Professional and Certified Information Systems Auditor interested in digital domains such as security management and artificial intelligence. He enjoys trail running, photography, video editing, and exploring the latest technological developments in his free time.